Biomarker concentrations and their temporal changes in patients with myocardial infarction and nonobstructive compared with obstructive coronary arteries: results from the PLATO trial - Hjort, Marcus; Eggers, Kai M.; Lakic, Tatevik Ghukasyan; Lindbäck, Johan; Budaj, Andrzej; Cornel, Jan Hein; Giannitsis, Evangelos; Katus, Hugo; Siegbahn, Agneta; Storey, Robert; Becker, Richard C.; Wallentin, Lars; et al. (Journal of the American Heart Association, 2023)
Background - - The pathobiology of myocardial infarction (MI) with nonobstructive coronary arteries (MINOCA) is often uncertain. Investigating biomarker concentrations and their changes may offer novel pathophysiological insights. - - Methods and Results - - In this post hoc study of the PLATO (Platelet Inhibition and Patient Outcomes) trial, concentrations of hs‐cTnT (high‐sensitivity cardiac troponin T), NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), hs‐CRP (high‐sensitivity C‐reactive protein), and GDF‐15 (growth differentiation factor 15) were measured in patients with MINOCA at baseline (n=554) and at 1‐month follow‐up (n=107). For comparisons, biomarkers were also measured in patients with MI with obstructive (stenosis ≥50%) coronary artery disease (baseline: n=11 106; follow‐up: n=2755]). Adjusted linear regression models were used to compare concentrations and their short‐ and long‐term changes. The adjusted geometric mean ratios (GMRs) in patients with MINOCA (median age, 61 years; 50.4% women) indicated lower hs‐cTnT (GMR, 0.77 [95% CI, 0.68-0.88]) but higher hs‐CRP (GMR, 1.21 [95% CI, 1.08-1.37]) and GDF‐15 concentrations (GMR, 1.06 [95% CI, 1.02-1.11]) at baseline compared with patients with MI with obstructive coronary artery disease, whereas NT‐proBNP concentrations were similar. Temporal decreases in hs‐cTnT, NT‐proBNP, and hs‐CRP concentrations until 1‐month follow‐up were more pronounced in patients with MINOCA. At follow‐up, patients with MINOCA had lower concentrations of hs‐cTnT (GMR, 0.71 [95% CI, 0.60-0.84]), NT‐proBNP (GMR, 0.45 [95% CI, 0.36-0.56]), and hs‐CRP (GMR, 0.68 [95% CI, 0.53-0.86]). One‐month GDF‐15 concentrations were similar between both groups with MI. - - Conclusions - - Biomarker concentrations suggest greater initial inflammatory activity, similar degree of myocardial dysfunction, and less pronounced myocardial injury during the acute phase of MINOCA compared with MI with obstructive coronary artery disease but also faster myocardial recovery. - - Registration - - URL: http://www.clinicaltrials.gov; Unique identifier: NCT00391872.
Gesehen am 13.06.2023
published online december 24, 2022